Dancing with the dragon : doing business with China - Chung, Mona. (International business collection., 2015)
China has passed through a tumultuous 20th century. This journey included moving from foreign domination to a Communist peasant revolution to the opening of its economy through "capitalist reforms" in the latter part of the 20th century. As we advance into the 21st century, China, to the surprise of many, appears in all the annals of economic advancement even reaching the milestone of the second largest economy in the world. Where it was once marginalised on the global stage, China today stands at the forefront of most economic international issues and developments. Much of the developed world is still getting used to this new milestone of China as a leader of the international community. This book provides a fresh and possibly unorthodox examination of a number of contemporary business issues in relation to the current role China plays. Besides examining China's global trade approach, the authors address China's unique investment approach in three major strategic destinations for China - Africa, Europe, and Australia. A special attention is given to the global financial crisis and its European version of this crisis. The authors also address some areas of "strategic mistrust" from global partners as exemplified in the handling of giant telecommunications provider Huawei in the United States highlighting new perspectives in the China-U.S. relationship. The book provides a different perspective of China's way about doing business with global partners offering new approaches to the way China, the dragon, dances in the centre stage with rotating dancing partners.